Effect of Thermocycling on the Bond Strength Between a Pure Commercially Titanium and Ceromer - Renato S. NISHIOKA; Alberto N. KOJIMA; Alfredo Mikail Melo MESQUITA; Rodrigo Othávio de Assunção e SOUZA; Luis Gustavo VASCONCELOS; Calos Augusto PAVANELLI (Association of Support to Oral Health Research (APESB), 2006)
Objective: To verify, using a shear mechanic test, the effect of the thermocycling on the bond strength between a pure commercially titanium (cpTi) and the esthetic veneer material (Resilab Wilcos/Brazil). Method: Twenty metallic cylinders (n=20), with 5mm of length and 4mm of diameter each one were obtained by machining of titanium bars. The metallic bars were sandblasted with aluminum oxide (250µm), at 2 bars of pressure for 20 seconds, with 3cm of distance. After was applied the adhesive system of the veneer material, Resibond (Wilcos/Brazil), and later the opaque Resilab and veneer on the metallic bases. The samples were stored in distilled water for 24 hours, at 37ºC and after randomly divided into 2 groups: G1 (control) and G2 (experimental), which was submitted to 500 thermocycles (5º/55ºC±1, dwell time: 30 s). The two groups were submitted to shear test in a universal testing machine (model DL-1000, EMIC Equipments and Systems Ltda., Sao Jose dos Pinhais - PR - Brazil) with a 500kg load cell at a speed of 0.5mm/min. The numeric dates (MPa) were submitted to the Mann-Whitney test (p=0.038). Results: After the dates analysis, was observed that the group G1 (7.83-18.72) was statistically different from the group G2 (5.51-15.34). Conclusion: Based on the results is lawful conclude that there was a significance reduction on the bond strength after thermocycling.